Calibration of the numerical model of a track section over a railway bridge based on dynamic tests. (December 2021) - Ribeiro, D.; Calçada, R.; Brehm, M.; Zabel, V.
Abstract: Progressive updating strategies are commonly used for the calibration of numerical models such as those of a track-bridge system. These strategies involve, first, updating the track model based on dedicated dynamic tests, and second, the calibration of the bridge model based on ambient vibration tests considering the updated track parameters. This subsequent procedure is suggested as some track parameters are, in relation to the modal responses of the bridge, generally not sufficiently sensitive for a successful parameter estimation. This work describes the calibration of a specific finite element (FE) model of a track section over a bowstring-arch railway bridge. The model includes the rails, rail pads, sleepers, the ballast layer and the interfaces with the bridge and neighbouring track sections. A track receptance test allowed for the identification of natural frequencies and mode shapes of the track by applying two different techniques, an output-only and an input-output. Several modes of vibration related to the movement of the sleepers on the ballast were identified using the SSI-DATA method, at frequencies between 83.8 Hz and 142.2 Hz. The calibration of the track FE model was performed using an iterative methodology by means of a genetic algorithm, which proves efficiency and robustness in estimating several track numerical parameters, besides a significant upgrade in relation to the numerical model before calibration.